The impact of peri‐operative blood transfusions on post‐pancreatectomy short‐term outcomes: an analysis from the American College of Surgeons National Surgical Quality Improvement Program. Issue 11 (24th August 2015) - Hallet, Julie; Mahar, Alyson L.; Tsang, Melanie E.; Lin, Yulia; Callum, Jeannie; Coburn, Natalie G.; Law, Calvin H. L.; Karanicolas, Paul J.
Abstract Background Peri‐operative red blood cell transfusions (RBCT) may induce transfusion‐related immunomodulation and impact post‐operative recovery. This study examined the association between RBCT and post‐pancreatectomy morbidity. Methods Using the American College of Surgeons National Surgical Quality Improvement Program (ACS‐NSQIP) registry, patients undergoing an elective pancreatectomy (2007–2012) were identified. Patients with missing data on key variables were excluded. Primary outcomes were 30‐day post‐operative major morbidity, mortality, and length of stay (LOS). Unadjusted and adjusted relative risks (RR) with a 95% confidence interval (95%CI) were computed using modified Poisson, logistic, or negative binomial regression, to estimate the association between RBCT and outcomes. Results The database included 21 132 patients who had a pancreatectomy during the study period. Seventeen thousand five hundred and twenty‐three patients were included, and 4672 (26.7%) received RBCT. After adjustment for baseline and clinical characteristics, including comorbidities, malignant diagnosis, procedure and operative time, RBCT was independently associated with increased major morbidity (RR 1.49; 95% CI: 1.39–1.60), mortality (RR 2.19; 95%CI: 1.76–2.73) and LOS (RR 1.27; 95%CI 1.24–1.29). Conclusion Peri‐operative RBCT for a pancreatectomy was independently associated with worse short‐term outcomes and prolonged LOS. Future studies should focus on the impact of interventions to minimize the use of RBCT after an elective pancreatectomy.